شبكة تسيير المخاطر: حلقة وصل بين التدقيق الداخلي و إدارة المخاطر دراسة حالة شركة متيجة للإسمنت - حواس محمد (جامعة الوادي University of Eloued, 2024)
This study aims to provide a summary of the literature related to risk management and risk management network in the first stage, and presenting the contributions of internal audit in activating the risk management device through the risk management network at the level of Al-Matidja Cement Company (S.C.MI – GICA), in a second stage. On this basis, our research was divided into two main axes: the first axis deals with the theoretical framework for risk management, and the second axis deals with risk management at the level of AlMatidja Cement Company (S.C.MI – GICA). Through the study presented, we reached a number of results, the most important of which is that the internal audit cell of the institution under study, in a first stage, prepares the annual audit program based on the risk management network and depending on the results of each task, the latter is updated, which contributed to activating risk management at the level of the latter
Risk Management Network: A link between internal audit and risk management-Case Study of Matidja Cement Company (S.C.MI - GICA)
Keywords: إدارة المخاطر; المراجعة الداخلية; شبكة تسيير المخاطر; Risk Management; internal audit; Risk management network